The U.S. Orange and Grapefruit Juice Markets: History, Development, Growth, and Change - Robert A. Morris (EDIS)
FE834, a 14-page illustrated fact sheet by Robert A. Morris, tells the story of the successes and failures in the U.S. citrus juice market. Includes references. Published by the UF Department of Food and Resource Economics, June 2010.